2009
DOI: 10.1016/j.bcp.2009.05.030
|View full text |Cite
|
Sign up to set email alerts
|

TC-5619: An alpha7 neuronal nicotinic receptor-selective agonist that demonstrates efficacy in animal models of the positive and negative symptoms and cognitive dysfunction of schizophrenia

Abstract: A growing body of evidence suggests that the alpha7 neuronal nicotinic receptor (NNR) subtype is an important target for the development of novel therapies to treat schizophrenia, offering the possibility to address not only the positive but also the cognitive and negative symptoms associated with the disease. In order to probe the relationship of alpha7 function to relevant behavioral correlates we employed TC-5619, a novel selective agonist for the alpha7 NNR subtype. TC-5619 binds with very high affinity to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
100
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(109 citation statements)
references
References 59 publications
7
100
1
1
Order By: Relevance
“…Indeed, studies have shown that drugs activating muscarinic or nicotinic acetylcholine receptor (nAChR) subtypes have potential for the treatment of cognitive symptoms in patients with schizophrenia (for review, see Jones et al, 2012). Specifically, nicotine, as well as agonists and positive allosteric modulators of a7 and a4b2 nAChRs, attenuate various cognitive deficits in rodent models of schizophrenia (Boess et al, 2007;Hashimoto et al, 2008;Hauser et al, 2009;Hurst et al, 2005;Pichat et al, 2007;Rushforth et al, 2011;Thomsen et al, 2009;Timmermann et al, 2007;Wallace et al, 2011;Wildeboer and Stevens, 2008;Wishka et al, 2006). Our observations that nicotine reverses the selective CMOR impairment in rats treated with subchronic NMDAR antagonists is consistent with studies using standard object recognition tasks and extends these findings by implicating nAChRs in the potential treatment of multisensory integration deficits in schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies have shown that drugs activating muscarinic or nicotinic acetylcholine receptor (nAChR) subtypes have potential for the treatment of cognitive symptoms in patients with schizophrenia (for review, see Jones et al, 2012). Specifically, nicotine, as well as agonists and positive allosteric modulators of a7 and a4b2 nAChRs, attenuate various cognitive deficits in rodent models of schizophrenia (Boess et al, 2007;Hashimoto et al, 2008;Hauser et al, 2009;Hurst et al, 2005;Pichat et al, 2007;Rushforth et al, 2011;Thomsen et al, 2009;Timmermann et al, 2007;Wallace et al, 2011;Wildeboer and Stevens, 2008;Wishka et al, 2006). Our observations that nicotine reverses the selective CMOR impairment in rats treated with subchronic NMDAR antagonists is consistent with studies using standard object recognition tasks and extends these findings by implicating nAChRs in the potential treatment of multisensory integration deficits in schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…This focus has led to the discovery of a number of distinct ␣7 agonists, including the spirofused quinuclidines (5S)-spiro[1,3-oxazolidine-5,8Ј-1-azabicyclo-[2.2.2]octane]-2-one (AR-R17779) (Mullen et al, 2000) and AZD-0328 (Sydserff et al, 2009), quinuclidine amides including PNU-282987 (Bodnar et al, 2005) (Wishka et al, 2006), TC-5619 (Hauser et al, 2009), and the related carbamate JN-403 (Feuerbach et al, 2009), SSR180711 (Biton et al, 2007;Pichat et al, 2007) Table 3 for details of potency. Roncarati et al, 2009), octahydro-pyrrolopyrrole A-582941 (Bitner et al, 2007;Tietje et al, 2008), and other yet undisclosed molecules (Taly et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Several other novel ␣7 nAChR agonists-(2R)-spiro-[1-azabicyclo[2.2.2]octane-3,2(3H)-furo [2,3-b]pyridine]-tartrate (AZD-0328) (Sydserff et al, 2009), 5-morpholin-4-yl-pentanoic acid (4-pyridin-3-yl-phenyl)-amide (SEN-12333/WAY-317538) (Roncarati et al, 2009) (Feuerbach et al, 2009), 2[2(4-bromophenyl)-2-oxoethyl]-1-methyl-pyridinium chloride (S24795) (Lopez-Hernandez et al, 2007), and N- [2-(pyridin-3-ylmethyl)-1-azabicyclo[2.2.2]oct-3-yl]-1-benzofuran-2-carboxamide (TC-5619) (Hauser et al, 2009)-have been recently described. Although these compounds have provided considerable insight supporting the involvement of ␣7 nAChRs in cognitive and learning functions, the majority of them have inherent limitations.…”
Section: Introductionmentioning
confidence: 99%
“…This compound also demonstrated a sufficient PK profile, with rapid CNS permeability, and activity in exploration in the rat social recognition model and an improved mouse sensory gating profile (DBA/2). Another amide quinuclidine compound (Targacept's [Winston-Salem, NC] TC-5619) demonstrated potency and selectivity for a7 nAChRs (net Therapeutic Potential of a7 nAChRs current EC 50 = 33 nM), with full efficacy relative to ACh in Xenopus oocytes (Hauser et al, 2009). TC-5619 (a7 nAChR K i = 1 nM) exhibited superior in vitro selectivity against human 5-HT 3 receptors (IC 50 .…”
Section: Gts-21mentioning
confidence: 99%